Alterações anatomopatológicas em aves de postura - Neiva, Débora Cantarin (2023)
The objective of the current study was to carry out a survey of the main anatomopathological alterations in chickens and raising quails and evaluate possible interference of these in the bone tissue. The study was approved by CEAU/UFES (n°014/2020). To obtain the data, 23 quails and 14 sick chickens were collected from farms in the central Serrana region of Espírito Santo and in the northwest region of Rio de Janeiro. Necropsies with macroscopic descriptions, microbiological, coproparasitological, radiographic and histomorphometric tests were carried out. It was done data descriptive analysis and average comparision using Student T test. In quails, that all of them showed injuries in the digestive system (100%), followed by urinary and reproductive (91%), muscular (78%), hematopoietic (56%), cardiorespiratory (30%) and bone system (8%) and the observed injuries were the altered collor of the liver (47%), pectoral muscle hypothophy (47%), splenic pallor (39%), fibrin deposition with cyst in oviduct (39%), intestinal serosa congestion (35%), ovarian hypotrophy (35%). In the parasitological exams, it was found oocysts of Eimeira sp. (39,13%). In the microbiological exams, it was detected predominantly Escherichia coli (83%), Klebsiella sp. (8,3%) and Pseudomonas aeruginosa with Salmonella spp. (16,6%). The Seedor Index (SI) was 22,85 e 23,56 mg/mm in tibia and femur, respectively, and the moderate level of osteopenia predominated in radiographic analysis. The percentage of trabecular bone in epiphysis of femurs and tibias was similar between healthy (22,1%) and sick (25,96%) quails and there wasn’t found alterations in the bone histology. Microscopically, it was observed lung congestion (91%) and hemorrhage (78%), kidney congestion (70%), liver congestion (61%), white stern hyperplasia in spleen (43%) e inflammation of the intestinal serosa (26%), and others. In chickens, it was found that all of them showed injury in digestive system (100%), followed by urinary and reproductive (78%), muscular (78%), cardiorespiratory (64%) and hematopoietic (64%) and the alterations observed were muscular (71%) and ovarian hypotrophy (64%), splenomegaly (50%), thickening in the intestinal wall (43%) and yellow kidneys (35%). In the parasitological exams, it was found oocysts of Eimeira sp. (50%) and helmints of the Order Ascaridida (50%). In the microbiological exams, it was detected Pasteurella spp. (21%) and Klebsiella sp. (7%). The Seedor Index was 99,2 e 118,5 mg/mm in tibia and femur, respectively, and the level of osteopenia varied from mild to moderate level in radiographic analysis. The percentage of trabecular bone in femurs and tibias was similar between healthy and sick chickens and there wasn’t found alterations in the bone histology. Microscopically, it was observed lung congestion (100%), lung hemorrhage, splenic congestion, liver congestion and inflammation, and others. It is concluded that in both species, there was predominance of alterations in the digestory system and mild parasitic infection. The most of macroscopic and histopatological lesions were compatible with those caused by infection of bacteria found in microbiological tests; being suggested the occurrence of colibacillosis and salmonellosis in quail, and avian cholera in chickens. Althoug, there was not interference of these anatomopathological changes in bone tissue in both poultry species.